An integrative medicine review of primary prevention of allergy in pediatrics - Henna Boolchandani; Randy Horwitz; Gary Soffer (Elsevier, 2021)
The prevalence of allergic disease has been rapidly increasing in the developed world for over fifty years. The prevention of allergic disease remains one of the most elusive topics in medicine. Integrative medicine emphasizes prevention of disease and utilizes many interventions to help modify long-term outcomes of health. Primary prevention refers to the arrest of manifestations of a disease before they present clinically. Preventing allergy is not simply about preventing sensitization, but also about developing tolerance. This narrative review article will discuss integrative medicine approaches that may help to prevent atopic disease in the pediatric population. It is organized chronologically to aid in counseling patients: 1) prevention during pregnancy and 2) prevention after birth. While research into allergy prevention is in its infancy, Integrative Medicine is well-suited to provide many insights into the prevention and mitigation of atopic disease.